Effect of castration and maturity on body glucose sensitivity, carcass composition, meat quality traits and muscle proteome and phosphoproteome of Nellore male cattle - Silva, Luiz Henrique Pereira (2018)
The current work consists of four manuscripts developed using the same animals.The objective of the first study aimed to evaluate the castration effect on carcass and meat traits of Nellore cattle harvested at different body weights (BW). Thirty-six Nellore (Bos taurus indicus) calves averaging 256.1 ± 3.05 kg of BW and 8.2 ± 0.07 months old were used, within then half was randomly selected for surgical castration one-week prior weaning. Weaned calves were fed with the same diet, and then six calves from each sex condition were randomly assigned to be harvested when the average BW of both sex conditions reaches 280, 380, and 480 kg. Therefore, this study was carried out as a complete randomized design following a 2 (sex condition) by 3 (weight at harvest) factorial arrangement of treatments. Beef traits were evaluated at 1, 7, and 14 d postmortem. Interaction effect was found (P < 0.01) for intramuscular fat and for kidney, pelvic and heart fat. Bull carcass was heavier (P < 0.05) than steer. Steer carcass had greater (P < 0.05) backfat thickness. Castration reduced shear force and increased myofibrillar fragmentation index at 14 d postmortem. Carcasses from cattle harvested at 480 kg had slower chilling, longer sarcomere, and lower shear force at 1 d postmortem. Shear force change from 1 d to 14 d postmortem reduced (P < 0.05) as harvest body weight increased. In conclusion, despite of carcass fatness, castration and body weight at harvest affect carcass and meat traits independently. The second study aimed to evaluate the glucose sensitivity of bulls and steers throughout body development. In addition, it was evaluated gene expression of biomarkers related to glucose metabolism, muscle growth and lipid deposition. Therefore, the same animals from the first study were used, and this study was carried out as a complete randomized design following a 2 (sex condition) by 3 (weight at harvest) factorial arrangement of treatments. Two glucose tolerance tests (GTT) were performed at 380 and 480 kg. Longissimus dorsi (LD) was sampled just after stunning for gene expression. Carcass composition and animal performance were evaluated. Bulls had greater final BW (P = 0.02) and tended to increase G:F ratio (P = 0.08) compared with steers. Bulls had greater carcass yield of lean (P = 0.02) and protein (P = 0.01) than steers. An interaction effect was found for carcass fat gain (P = 0.01), and steers gained more carcass fat than bulls only from 380 to 480 kg of BW. Carcass protein fractional accretion rate (FAR) decreased as cattle BW increased (P < 0.01). Neither glucose basal level nor area under the curve (AUC) post-infusion were affected by castration or cattle BW (P > 0.05). Expression of genes related to glucose metabolism in the LD were not affected by castration or cattle BW (P > 0.05). Castration tended (P = 0.086) to upregulate LD expression of Acetyl-CoA carboxylase alpha (ACACA). Interaction effects (P < 0.05) were found for LD expression of IGF-1 receptor (IGF1R) and F-box protein 32 (FBXO32), and for both genes steers had the greatest mRNA abundance at 380 kg while bulls had the greatest abundance at 480 kg of BW. The LD expression of serpin A3-6 tended (P = 0.08) to be downregulated as cattle BW increased from 280 to 480 kg. In conclusion, despite of the carcass fatness enhancement by castration and increasing BW, Nellore cattle whole-body sensitivity to glucose does not change. For the third study, the LD sampled at the harvest were used to compare the proteome and phosphoproteome of Nellore bulls and steers during different growth stages. Extracted muscle protein was separated in a 2D-PAGE and stained sequentially with Pro- Q Diamond and Colloidal Coomassie. Afterward, a comparative analysis of protein profile was performed, and differentially abundant protein spots were excised for protein identification by MALDI-TOF/TOF. Castration affected (P < 0.05) abundance of 6 phosphoproteins and 10 protein spots, while body weight affected (P < 0.05) abundance of 34 phosphoproteins and 29 protein spots. Castration decreased (P < 0.05) the abundance of two glycolytic enzymes of the energy-yielding phase, suggesting that glycolysis pathway enhanced glycerol-3P supply for a greater fat deposition on steers. Regarding the growth stage, despite the structural proteins myosin regulatory light chain 2 (MYLPF), and actin alpha 1 (ACTA1), most of identified proteins were related to energy metabolism, including glycogen metabolism, glycolysis, oxidative phosphorylation, creatine- phosphate metabolism, and cytosolic NADH metabolism. These results suggest that decreasing muscle growth rate decreases muscle glycolysis and ATP generation. The fourth study used only the twelve Nellore cattle harvested at 480 kg of BW. The aim of this study was to evaluate the differential proteome and phosphoproteome between bulls and steers during conversion of muscle to meat, as well as after 14 d of aging. Twelve male Nellore calves were used (247 kg, and 8 months old) and six calves were randomly selected for surgical castration one week before weaning. Post-weaning calves were fed the same diet and were harvested after 230 d on feeding. Longissimus muscle was sampled just after stunning (0d postmortem), at deboning (1d postmortem) and after aging (14d postmortem) for proteome analysis. The carcass traits were evaluated at deboning and meat shear force was measured at 1, 7, and 14 d postmortem. Muscle protein extract was separated by 2D-PAGE and stained sequentially for phosphoprotein (Pro-Q Diamond) and for total protein (Colloidal Coomassie). Differentially abundant protein spots between sex condition or across postmortem time were excised for protein identification by MALDI- TOF/TOF. Castration upregulated (P < 0.05) the abundance of glycolytic enzymes, while the oxidative phosphorylation protein ATP5B was downregulated (P < 0.05). In addition, abundance of troponin T fast isoform (TNNT3) was upregulated by castration (P < 0.05), while the slow isoform (TNNT1) tended to decrease (P < 0.10) abundance. The creatine kinase M-type was markedly fragmented postmortem. Abundance of phosphorylated PGM1 increased during the first 24 h postmortem and was highly correlated with carcass pH. The abundance of one spot of heat shock cognate 71 kDa protein (HSC70) markedly increased after aging. Further, abundance of the phosphorylated myofibrillar proteins ACTA1 and MYLPF were positively correlated with sarcomere shortening. In conclusion, our finds demonstrated that abundance and phosphorylation of glycolytic enzymes affect meat quality during conversion of muscle to meat. Overall, castration markedly increased carcass fatness and intramuscular fat, whereas whole body glucose sensitivity and conversion of muscle to meat seems to be similar between bulls and steers.